The prayers and tears of Jacques Derrida : religion without religion - Caputo, John D. (Indiana series in the philosophy of religion., 1997)
Caputo's book is riveting ... A singular achievement of stylistic brio and impeccable scholarship, it breaks new ground in making a powerful case for treating Derrida as homo religiosis ... There can be no mistaking the importance of Caputo's work." 'Edith Wyschogrod No one interested in Derrida, in Caputo, or in the larger question of postmodernism and religion can afford to ignore this pathbreaking study. Taking full advantage of the most recent and least discussed writings of Derrida, it offers a careful and comprehensive account of the religious dimension of Derrida's thought." 'Merold Westphal.